An investigation into the impact of residual reagents on flotation in response to process water recirculation - Khan, Saahil (Department of Chemical Engineering, 2024)
In the mineral pulp phase of the flotation process, water makes up about 80-85% of the constituents, thus making water an important component. The increasing scarcity of water has resulted in greater environmental restrictions which have led to the necessity of mine operations recycling water from tailing dams, thickener overflow, dewatering and filter products. However, water quality is found to influence the process of ore flotation, the results of various studies investigating the effects of water and recirculating water have seen an adverse effect on flotation selectivity. The particular focus of the study was to consider the impact of dewatering reagents which may have been present in water recycled from the tailings back into the flotation process. The ore was from the Merensky reef which is found in the Bushveld Igneous Complex (BIC). The complex contains the world largest deposits of platinum group elements. About 75% of the world's platinum reserves and 50% of the world's palladium reserves are in the bushveld igneous complex, making it one of the most economically significant mineral deposit complexes in the world. The primary dewatering reagents considered were flocculants and coagulants. There are two mechanisms by which flocculation occurs: the polymer bridging theory and the patch model. Polyacrylamides (PAM) are the most common flocculants. Coagulants use a charge neutralisation mechanism to take effect with the most common type being used are salts containing highly charged cations such as Al 3+ and Fe3+ . The experimental design chosen was a factorial with midpoint analysis. Three factors that were considered at varying dosages; the depressant, flocculant and coagulant. The two levels were high and low (where low was no addition of the respective reagent and high was equivalent to the concentrate seen on site recirculated process water). The key performance parameters used to determine effects were solid recovery, water recovery, copper and nickel mineral recovery, copper and nickel mineral grade, residual concentrations of collector and depressant pre and post flotation as well as particle settling of the tails. For all test conditions relative to the base condition where none of the varied reagents were added, the solid and water recovery increased, the nickel recovery increased slightly while its grade decreased, the copper recovery was unaffected, but the grade decreased, there was no impact on the residual concentration of the collector and depressant pre and post flotation. The settling of the tailings also remained unaffected. The solids and water recovery increased due to the agglomeration of finer particles in the system which resulted in the particles having better momentum for particle bubble attachment and faster recovery rates. There may have been a slight effect of the increase in ionic concentration of the water caused by the presence of additional reagents which resulted in a more stable froth and may have increased the recoveries of the solids. The recoveries of the value bearing minerals did not change, the grade however decreased because the increase in solids recoveries is attributed to increased gangue recovery owing to the fine particle size, which, in the presence of dewatering agents would have a faster recovery rate. The residual reagents concentration did not change as the primary impact on their adsorption would have iv been a change in the surface area due to an increase in particle size, which was not varied by grinding in this study. However, owing to the addition of dewatering agents, the particles may have agglomerated and hence become larger. The depressant adsorption may have been unimpacted owing to the inability of the depressant to fully cover the particle surfaces under standard flotation conditions. The collector adsorption was unimpacted and this is assumed to be owing to the concentration of the dewatering agents used within this study not being high enough to compete with the collector for mineral surface area. The settling of the tails remained unaffected as the finer particles which, in the presence of dewatering agents reported to the concentrate and had little impact on the composition of the tails. It can be deduced from the results that the possible introduction of the dewatering reagents into the flotation system due to recycling of tailings water may be detrimental to the system. The primary impact of flocculants and coagulants in the flotation process was the introduction of more gangue in the concentrate which decreases the grade of the concentrate and will need to be further refined downstream. Furthermore, there is no positive impact on the settling of the tails, implying that the flocculant and coagulant action is suppressed during flotation and further flocculant and coagulant would need to be added during dewatering but may need careful screening prior to the recirculated water entering the milling and flotation stages for a mineral processing circuit